Odorant and pheromone receptors in insects - HA, TAL S.; Smith, Dean p. (Frontiers in Cellular Neuroscience, 2009)
Since the emergence of the first living cells, survival has hinged on the ability to detect and localize chemicals in the environment. Modern animal species ranging from insects to mammals express large odorant receptor repertoires to detect the structurally diverse array of volatile molecules important for survival. Despite the essential nature of chemical detection, there is surprising diversity in the signaling mechanisms that different species use for odorant detection. In vertebrates, odorant receptors are classical G-protein coupled, seven transmembrane receptors that activate downstream effector enzymes that, in turn, produce second messengers that open ion channels. However, recent work reveals that insects have adopted different strategies to detect volatile chemicals. In Drosophila, the odorant receptors, predicted to have seven transmembrane domains, have reversed membrane topology compared to classical G-protein coupled receptors. Furthermore, insect odorant receptors appear to form odorant-gated ion channels. Pheromone detection in insects is even more unusual, utilizing soluble, extracellular receptors that undergo conformational activation. These alternate olfactory signaling strategies are discussed in terms of receptor design principles.